Pengaruh Bentuk Rangkaian Panel Surya Terhadap Kuat Arus, Tegangan dan Daya - Pande Putu Agus Santoso; Feby Nopriyandy; Irma Fahrizal Butsi Ningsih; Leo Dedy Anjiu; Indra Kurniawan (Jurnal Engine: Energi, Manufaktur, dan Material, 2022)
The purpose of this study was to determine the effect of solar panel circuits on current, voltage and power. This research is a true experiment. Dependent variables were current, voltage, and power. Independent variables were a series circuit of solar panels and a parallel circuit of solar panels. The sample numbers of studies were 12 for each group of independent variables. The data were analyzed using the t-test at the 5% signification level. The results showed that the electrical power produced by a series circuit of solar panels was, P = 4.81 watt, Sd = 0.24. The electrical power produced by a parallel circuit of solar panels was P = 4.69 watts, Sd = 0.13. The t-test showed that there was no difference in electrical power produced by the series circuit of solar panels and parallel circuit of solar panels, with to = 1.525 < tα/2, v =2,074. The form of a circuit (series or parallel) has no significant effect on power but differs only in current and voltage. In series circuit, I1 = I2 = IΣ and V1 +V2 = VΣ. In parallel circuits V1 = V2 = VΣ and I1 + I2 = IΣ. This can be adjusted to our purpose of using solar panels circuit. If it requires a large current, the solar panels must assemble in a parallel circuit. But if it requires a large voltage, the solar panels must assemble in a series circuit.Keywords: current, parallel, power, series, voltage